2019
DOI: 10.3390/ijms20194875
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen and Red Blood Cells Impact Umbilical Cord Blood CD34+ Cell Viability after Thawing

Abstract: Hematopoietic progenitor cell (HPC) transplantation is a treatment option for malignant and nonmalignant diseases. Umbilical cord blood (UCB) is an important HPC source, mainly for pediatric patients. It has been demonstrated that human leukocyte antigen (HLA) matching and cell dose are the most important features impacting clinical outcomes. However, UCB matching is performed using low resolution HLA typing and it has been demonstrated that the unnoticed mismatches negatively impact the transplant. Since we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, CD34+ cell viability was significantly higher in the STCB group. It has been reported that TNC, viable CD45+ and CD34+ cells have a statistically significant correlation with CD34 viability after thawing [22]. In addition, a recent study suggested that CB transplantation with low TNC but high CD34+ cells was associated with enhanced engraftment [23].…”
Section: Discussionmentioning
confidence: 98%
“…However, CD34+ cell viability was significantly higher in the STCB group. It has been reported that TNC, viable CD45+ and CD34+ cells have a statistically significant correlation with CD34 viability after thawing [22]. In addition, a recent study suggested that CB transplantation with low TNC but high CD34+ cells was associated with enhanced engraftment [23].…”
Section: Discussionmentioning
confidence: 98%
“…The TNC and CD34 + cells in the UCB unit were limited. However, UCB had a less mature phenotype of CD34 + progenitors compared to adult marrow and peripheral blood grafts, which might have a higher proliferation potential than adult CD34 + cells [ 31 ]. Taken together, the UCB unit, as one of the grafts for allo-HSCT, could reduce the GVHD effect, enhance the GVL effect and promote engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…There is an important experience in Colombia with UCB transplantation for pediatric patients and a higher inventory of cord blood donors with HLA high-resolution typing available in the public UCB bank which started 5 years ago (11). Since there is no unrelated bone marrow donor registry in the country, UCB turns out an important source along with haploidentical donors for patients who require transplantation.…”
Section: Introductionmentioning
confidence: 99%